CONCEPT OF AIR CARGO SYSTEM OPERATION AND WAYS OF ITS INSPECTION AND SAFETY PROVISION - Ivannikova, V.; Manziuk, T. (Science-based technologies, 2012)
In this article the notion of air cargo system operation is being studied. Also there are considered such procedures of air cargo processing as inspection and security. The detailed research proofed the significance of inspection devices installation in the air cargo complex as the main factor in security maintenance.